Metastable beta titanium alloy with yield ratio lower than 0.6 and preparation method of metastable beta titanium alloy
By introducing stresses on the interface with thin ω phase adhered to the interface in the metastable β-titanium alloy, the ω phase strips and/or {332}<113> deformation twins are induced, which reduces its yield-strength ratio and solves the yield-strength in the prior art The problem of high strength ratio improves the work hardening ability and plasticity of the material, and is suitable for cold-formed parts for aviation.
Patent Information
- Application Number
- CN202411518729.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The yield ratio of existing metastable β-titanium alloys is relatively high, resulting in difficulty in cold deformation and insufficient strength, which limits its application in cold-formed components for aviation.
By rationally designing the chemical composition of metastable β-titanium alloy, the stress of thin ω phase attached to the interface is introduced to induce ω phase strips and/or {332}<113> deformation twins, reducing the yield-strength ratio, improving work hardening capabilities and Plasticity.
The yield ratio is lower than 0.6, which significantly improves the work hardening ability and plasticity of the material. It is suitable for the manufacture of high-strength cold-formed parts for aviation aircraft.
Smart Images

Figure CN119242988A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium alloy materials, and in particular relates to a metastable beta titanium alloy with a yield ratio lower than 0.6 and a preparation method thereof. Background Art
[0002] Titanium alloy has high specific strength and excellent corrosion resistance, and is an important material for aviation structures. The use of titanium alloy to manufacture aircraft load-bearing structural parts can not only greatly reduce the overall structural weight of the aircraft, but also significantly improve fuel efficiency and extend service life. For titanium alloy sheets formed by cold deformation, their size limit is much greater than that of titanium alloy sheets formed by heated forging. At the same time, their forming efficiency is high and the cost is low, which can easily meet the design and application requirements of large-size aircraft structural parts. Cold deformation requires the material to have a low yield strength for easy deformation, high plasticity to prevent cracking during deformation, and significant work hardening ability to ensure that high tensile strength can be obtained after deformation, that is, the material is required to have a low yield strength ratio (the ratio of yield strength to tensile strength). In addition, a low yield strength ratio can also improve the failure resistance and vibration resistance of the material after yielding and before plastic instability, and improve the reliability of the material during service.
[0003] As a high-dislocation material, titanium alloy generally has the problem of insufficient work hardening ability, resulting in a high yield ratio (close to 1.0). Relevant studies in recent years have shown that metastable β titanium alloys with very low β matrix stability have high work hardening ability due to the ability to produce phase transformation and / or twin-induced plasticity effect during deformation, making it a type of titanium alloy with the lowest yield ratio. However, it is worth noting that the phase transformation-induced plasticity effect in most of the current metastable β titanium alloys depends on the stress-induced β→α” martensite phase transformation. Due to the limited hindering effect of α” martensite on dislocation movement, the yield ratio of existing metastable β titanium alloys is generally higher than 0.7, and the yield ratio of a few metastable β titanium alloys that can produce very hard α” martensite is not less than 0.63, which limits the further application of this type of alloy in the field of cold-formed parts for aviation.
[0004] Related studies have found that compared with α" martensite, ω phase and {332} <113> Twins have a stronger barrier effect on dislocations. In addition, by <113> By regulating the interface structure of the twins, a thin layer of ω phase is generated at the interface of the ω phase lath and the twins, which can further improve its ability to hinder dislocations. Therefore, by rationally designing the composition of the metastable β titanium alloy, it is easy to produce stress-induced ω phase laths and / or {332} with a thin layer of ω phase attached to the interface during deformation. <113> Deformation twinning is the key way to solve the problem of high yield strength ratio of existing metastable β titanium alloys.
[0005] Based on this, the present invention provides a metastable β titanium alloy with a yield ratio lower than 0.6 and a preparation method thereof. Summary of the invention
[0006] Considering that the existing metastable β titanium alloy has a high yield strength ratio, which makes it difficult to cold deform or has insufficient strength after cold deformation, and is prone to premature failure during service, a stress-induced ω phase lath or {332} <113> Deformation twinning can effectively improve its work hardening ability and plasticity and significantly reduce its yield strength ratio. Therefore, the alloy composition is rationally controlled to produce stress-induced ω phase laths and / or {332} <113> Deformation twinning is a key approach to solving the problem of high yield strength ratio of existing metastable β titanium alloys.
[0007] The deformation mechanism of metastable β titanium alloy is closely related to the shear modulus of its β matrix in a specific direction, which is directly affected by the alloy composition. By rationally designing the chemical composition of metastable β titanium alloy, such as using V as the main alloying element and controlling its content within a specific range, the β matrix can generate stress-induced ω phase laths and / or {332} <113> Deformation twins, and on this basis, adding Fe can further regulate the interface structure of ω phase laths and twins, so that a thin layer of ω phase is produced at the interface. Stress-induced ω phase laths or {332} <113> The massive formation of deformation twins can effectively reduce the mean free path of dislocations and promote the accumulation of dislocations, thereby improving the work hardening ability and plasticity of the corresponding alloys and significantly reducing the yield strength ratio of the alloys.
[0008] Based on the above considerations, the present invention aims to solve the problem of high yield ratio of existing metastable β titanium alloys and provide a metastable β titanium alloy with a yield ratio lower than 0.6 and a preparation method thereof.
[0009] Specifically, the first aspect of the present invention provides a metastable β titanium alloy with a yield ratio lower than 0.6, wherein the constituent elements and mass percentages of the titanium alloy are: 78%~82% Ti, 18%~20% V, 0.5%~1% Fe, 0.03%~0.08% O, and the remainder is unavoidable impurity elements.
[0010] As a further illustration of the present invention, the titanium alloy is composed of 100% β phase and produces stress-induced ω phase laths with thin layers of non-same variant ω phase attached to the boundaries and / or a thin layer of ω phase attached to the twin boundaries {332} <113> Deformation twins.
[0011] As a further illustration of the present invention, the mass percentage ratio of the Ti element to the V element in the titanium alloy is in the range of 4 to 4.5, and the sum of 0.67 times the mass percentage of the V element and 2.9 times the mass percentage of the Fe element is in the range of 13.6% to 16.3%, so as to ensure that the titanium alloy can obtain 100% of the β phase with lower stability after solution quenching, and the shear modulus of the β phase in a specific direction is in a suitable range, so that the titanium alloy can generate a large number of stress-induced ω phase laths and / or {332} during plastic deformation. <113> Deformation twins.
[0012] As a further illustration of the present invention, the mass percentage ratio of the V element to the Fe element in the titanium alloy is in the range of 18 to 35, so as to ensure that the stress-induced ω phase lath or {332} generated by the titanium alloy during the plastic deformation process <113> A thin layer of ω phase will be formed on the boundary of the deformation twin, which will produce a very strong ability to hinder the movement of dislocations, thereby making the titanium alloy exhibit a very strong work hardening ability.
[0013] As a further illustration of the present invention, the sum of the mass percentages of Fe and O in the titanium alloy is not higher than 1.05%, so as to ensure that the titanium alloy exhibits a sufficiently low yield strength, thereby being easy to cold deform and obtaining a low yield strength ratio.
[0014] As a further illustration of the present invention, the mass percentages of interstitial impurity elements H, N, and C in the titanium alloy are respectively less than 0.004%, 0.015%, and 0.02%, so as to ensure that the titanium alloy undergoes stress-induced β→ω phase transformation or {332} <113> The motion of the atoms involved in twinning is not completely blocked by interstitial impurity atoms.
[0015] A second aspect of the present invention provides a method for preparing the above-mentioned metastable β titanium alloy having a yield ratio lower than 0.6, comprising the following steps: S1. Weigh pure Ti, pure V and pure Fe raw materials according to the constituent elements and mass percentages of the titanium alloy in any one of claims 1 to 4, and obtain a titanium alloy ingot by vacuum arc melting; S2, performing vacuum homogenization annealing treatment on the titanium alloy ingot; S3, hot rolling the titanium alloy ingot after vacuum homogenization annealing to form a hot-rolled plate, water-cooling and quenching to room temperature after hot rolling, and then performing multiple cold rolling processes on the hot-rolled plate to form a cold-rolled plate; S4, performing vacuum solution heat treatment on the cold-rolled plate, and after the solution treatment, water-cooling and quenching to room temperature to complete the preparation of the titanium alloy.
[0016] As a further illustration of the present invention, in S1, the raw materials are pure Ti, pure V and pure Fe with a purity higher than 99.95%, and are proportioned according to the mass percentage of each element.
[0017] As a further illustration of the present invention, in S1, vacuum arc melting is repeated 3 to 5 times, and after each melting is completed, the titanium alloy ingot is turned over for the next melting.
[0018] As a further illustration of the present invention, in S2, the titanium alloy ingot is placed in a vacuum higher than 3×10 -4 The temperature is raised with the furnace in a vacuum environment of 1000 Pa, kept at 1050°C for more than 10 hours, and then cooled with the furnace to room temperature.
[0019] As a further illustration of the present invention, in S3, the titanium alloy ingot after vacuum homogenization annealing is placed in a vacuum chamber with a degree of vacuum higher than 3×10 -4 Pa vacuum environment with the furnace temperature rise, after being kept at 900 ℃ for more than 30min, it is immediately hot rolled on a double-roll strip mill with a deformation of 30%~60%. After hot rolling, it is water-cooled and quenched to room temperature.
[0020] As a further illustration of the present invention, in S3, the hot-rolled plate is subjected to multiple cold rolling passes at room temperature using a twin-roll strip mill, the roller pressure in each pass does not exceed 0.3 mm, and the total deformation is 30% to 70%.
[0021] As a further illustration of the present invention, in S4, the cold-rolled sheet is placed in a vacuum higher than 1×10 -3 Pa vacuum environment, kept at 800℃~900℃ for 30min, and then water-quenched to room temperature.
[0022] As a further illustration of the present invention, after the vacuum solution heat treatment described in step S4, the microstructure of the titanium alloy material is an equiaxed β grain structure with an average grain size in the range of 80 μm to 150 μm.
[0023] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention prepares a metastable β titanium alloy with a yield strength ratio lower than 0.6 through reasonable composition design and fine control of the preparation process. The titanium alloy can produce stress-induced ω phase laths with a non-identical variant ω phase thin layer attached to the boundary and / or a thin layer of ω phase attached to the twin boundary during plastic deformation. <113> Deformation twins. This interface has a thin layer of ω phase attached to it, which is a stress-induced ω phase lath or {332} <113> Deformation twins have a very strong ability to hinder dislocation movement, which can greatly improve the work hardening ability and plasticity of the corresponding alloy and significantly reduce the yield strength ratio of the alloy. The titanium alloy provided has a tensile strength of more than 690MPa and a fracture elongation of more than 36% under the condition of a yield strength not exceeding 460MPa, and a yield strength ratio of less than 0.6. Under the optimal composition ratio, its yield strength ratio can be further reduced to 0.51, which is suitable for manufacturing cold-formed high-strength parts for new aircraft. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the backscattered electron image of the initial structure of the titanium alloy prepared in Examples 1 and 2 of the present invention and Comparative Example 3.
[0025] Figure 2 1 and 2 and comparative example 3 of the present invention, respectively.
[0026] Figure 3 The electron backscatter diffraction patterns of the deformed structures of the titanium alloys prepared in Examples 1 and 2 and Comparative Example 3 of the present invention are shown.
[0027] Figure 4 The electron backscattered diffraction patterns of deformation bands in the deformation structures of the titanium alloys prepared in Examples 1 and 2 of the present invention and Comparative Example 3 are shown. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Aiming at the problem that the yield ratio of existing metastable β titanium alloy is too high, the present invention provides a metastable β titanium alloy with a yield ratio lower than 0.6. The constituent elements and mass percentages of the titanium alloy are: 78%-82% Ti, 18%-20% V, 0.5%-1% Fe, 0.03%-0.08% O, and the remainder is inevitable impurity elements.
[0030] Specifically, in the above-mentioned titanium alloy, the mass percentage of the Ti element can be, for example, 78%, 79%, 80%, 81%, 82%, or any point value between the above two values, etc.; the mass percentage of the V element can be, for example, 18%, 19%, 20%, or any point value between the above two values, etc.; the mass percentage of the Fe element can be, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or any point value between the above two values, etc.; the mass percentage of the O element can be, for example, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, or any point value between the above two values, etc.
[0031] Furthermore, the mass percentage ratio of the Ti element to the V element in the above titanium alloy is in the range of 4 to 4.5, for example, it can be 4, 4.1, 4.2, 4.3, 4.4, 4.5, or any point value between the above two values, etc.; and the sum of 0.67 times the mass percentage of the V element and 2.9 times the mass percentage of the Fe element is in the range of 13.6% to 16.3%, for example, it can be 13.6%, 14%, 15%, 16%, 16.3%, or any point value between the above two values, etc., to ensure that the titanium alloy can obtain 100% of the β phase with lower stability after solution quenching, and the shear modulus of the β phase in a specific direction is in an appropriate range, so that the titanium alloy can generate a large number of stress-induced ω phase laths and / or {332} during plastic deformation. <113> Deformation twins.
[0032] The mass percentage ratio of the V element to the Fe element in the titanium alloy is in the range of 18 to 35, for example, 18, 20, 23, 25, 27, 30, 32, 35, or any point value between the above two values, so as to ensure that the stress-induced ω phase lath or {332} generated by the titanium alloy during the plastic deformation process is <113> A thin layer of ω phase will be formed on the boundary of the deformation twin, which will produce a very strong ability to hinder the movement of dislocations, thereby making the titanium alloy exhibit a very strong work hardening ability.
[0033] The sum of the mass percentages of Fe and O in the titanium alloy is not higher than 1.05%, for example, it can be 0.53%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.05%, or any point between the above two values, etc., to ensure that the titanium alloy has a sufficiently low yield strength, thereby being easy to cold deform and obtaining a low yield strength ratio.
[0034] The mass percentages of interstitial impurity elements H, N, and C in titanium alloys are less than 0.004%, 0.015%, and 0.02%, respectively, to ensure that the titanium alloy undergoes stress-induced β→ω phase transformation or {332} <113> The motion of the atoms involved in twinning is not completely blocked by interstitial impurity atoms.
[0035] The method for preparing the above-mentioned metastable β titanium alloy having a yield ratio lower than 0.6 comprises the following steps: S1. Weigh pure Ti, pure V and pure Fe raw materials according to the constituent elements and mass percentages of the above-mentioned titanium alloy, and obtain a titanium alloy ingot by vacuum arc melting.
[0036] In S1, the raw materials are pure Ti, pure V and pure Fe with a purity higher than 99.95%, and the ingredients are prepared according to the mass percentage of each element. The vacuum arc melting is repeated 3 to 5 times, and after each melting, the titanium alloy ingot is turned over for the next melting.
[0037] S2. Perform vacuum homogenization annealing on the titanium alloy ingot.
[0038] In S2, the titanium alloy ingot is placed in a vacuum higher than 3×10 -4 The temperature is raised with the furnace in a vacuum environment of 1000 Pa, kept at 1050°C for more than 10 hours, and then cooled with the furnace to room temperature.
[0039] S3, hot rolling the titanium alloy ingot after vacuum homogenization annealing to form a hot-rolled plate, quenching it with water to room temperature after hot rolling, and then performing multiple cold rolling processes on the hot-rolled plate to form a cold-rolled plate.
[0040] In S3, the titanium alloy ingot after vacuum homogenization annealing is placed in a vacuum chamber with a degree of vacuum higher than 3×10 -4 Pa vacuum environment with the furnace temperature rise, after more than 30min of heat preservation at 900℃, then immediately use a double-roller plate and strip mill to carry out a single hot rolling, the deformation is 30%~60%, after hot rolling is completed, water-cooled quenching to room temperature. At room temperature, the hot-rolled plate is cold-rolled for multiple passes using a double-roller plate and strip mill, the roller pressure of each pass does not exceed 0.3mm, and the total deformation is 30%~70%.
[0041] S4. The cold-rolled plate is subjected to vacuum solution heat treatment, and after the solution treatment, it is water-cooled and quenched to room temperature to complete the preparation of the titanium alloy.
[0042] In S4, the cold rolled sheet is placed in a vacuum higher than 1×10 -3 Pa vacuum environment, kept at 800℃~900℃ for 30min, and then water-quenched to room temperature.
[0043] After the vacuum solution heat treatment in step S4, the microstructure of the titanium alloy material is an equiaxed β grain structure with an average grain size in the range of 80 μm to 150 μm.
[0044] The following describes in conjunction with specific embodiments: Example 1
[0045] The main constituent elements and mass percentages of the metastable β titanium alloy with a yield ratio lower than 0.6 provided in this embodiment are: 80.4% Ti, 18.95% V, 0.58% Fe, 0.036% O, 0.0023% H, 0.011% N, 0.02% C, and the remainder are unavoidable impurity elements.
[0046] The preparation process of this titanium alloy includes the following steps: S1. Using high-purity Ti with a purity of 99.995%, high-purity V with a purity of 99.95%, and high-purity Fe with a purity of 99.95% as raw materials, smelting is performed in a vacuum arc melting furnace, and the smelting is repeated 5 times. After each smelting is completed, the titanium alloy ingot is turned over for the next smelting; S2, seal the titanium alloy ingot into a glass tube, the vacuum degree of the glass tube is 3.5×10 -4 Pa, the sealed titanium alloy ingot is placed in a resistance furnace, first heated to 1050°C, kept at this temperature for 12 hours for vacuum homogenization annealing, and then cooled to room temperature; S3. Place the glass tube containing the titanium alloy ingot after vacuum homogenization annealing in a resistance furnace, first heat it to 900°C with the furnace, keep it at this temperature for 30 minutes, then quickly smash the glass tube, use a double-roll plate and strip mill to hot-roll the titanium alloy ingot once, with a total deformation of 53.8%, and water-cooled and quenched to room temperature after hot rolling. Then use a double-roll plate and strip mill to cold-roll the hot-rolled titanium alloy plate for multiple passes at room temperature, with the roller pressure of each pass being 0.3mm, and the total deformation being 64.7%; S4, the cold-rolled titanium alloy sheet is sealed in a glass tube, and the vacuum degree of the glass tube is 1×10 -3 Pa, the sealed titanium alloy plate was placed in a resistance furnace, kept at 830 °C for 30 min, and then quenched by water cooling to room temperature.
[0047] The initial structure of the titanium alloy prepared in this example was characterized by scanning electron microscopy. Figure 1 The results show that the initial structure of the titanium alloy prepared in this embodiment is an equiaxed β grain structure with an average grain size of 102.7±0.9μm.
[0048] The mechanical properties of the titanium alloy prepared in this embodiment were tested according to GB / T 228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method". The engineering stress-engineering strain curve is shown in the attached figure. Figure 2 The results show that the upper yield strength of the alloy is 401±33MPa, the lower yield strength is 367±14MPa, the tensile strength is 713±1MPa, the elongation at break is 41±8%, and the yield strength ratio is 0.51.
[0049] The electron backscatter diffraction of the scanning electron microscope was used to characterize the deformation structure of the titanium alloy prepared in this embodiment. Figure 3 The results show that the dominant deformation mechanism of the alloy is stress-induced β→ω phase transformation, {332} <113> Twinning and dislocation slip.
[0050] The electron backscatter diffraction of the scanning electron microscope was used to characterize the deformation band in the deformation structure of the titanium alloy prepared in this embodiment. Figure 4 The results show that a thin layer of ω phase is attached to the boundary of the stress-induced ω phase lath formed during the plastic deformation of the alloy, and this ω phase belongs to a different variant from the internal stress-induced ω phase lath. Example 2
[0051] The main constituent elements and mass percentages of the metastable β titanium alloy with a yield ratio lower than 0.6 provided in this embodiment are: 79.61% Ti, 19.35% V, 0.94% Fe, 0.07% O, 0.0011% H, 0.007% N, 0.014% C, and the remainder are unavoidable impurity elements.
[0052] The preparation process of this titanium alloy includes the following steps: S1. Using high-purity Ti with a purity of 99.995%, high-purity V with a purity of 99.95%, and high-purity Fe with a purity of 99.95% as raw materials, smelting is performed in a vacuum arc melting furnace, and the smelting is repeated 5 times. After each smelting is completed, the titanium alloy ingot is turned over for the next smelting; S2, seal the titanium alloy ingot into a glass tube, the vacuum degree of the glass tube is 3.5×10 -4 Pa, the sealed titanium alloy ingot is placed in a resistance furnace, first heated to 1050°C, kept at this temperature for 12 hours for vacuum homogenization annealing, and then cooled to room temperature; S3. Place the glass tube containing the titanium alloy ingot after vacuum homogenization annealing in a resistance furnace, first heat it to 900°C with the furnace, keep it at this temperature for 30 minutes, then quickly smash the glass tube, use a double-roll plate and strip mill to hot-roll the titanium alloy ingot once, with a total deformation of 39.7%, and water-cooled and quenched to room temperature after hot rolling. Then use a double-roll plate and strip mill to cold-roll the hot-rolled titanium alloy plate for multiple passes at room temperature, with the roller pressure of each pass being 0.3mm and the total deformation being 67.4%; S4, the cold-rolled titanium alloy sheet is sealed in a glass tube, and the vacuum degree of the glass tube is 1×10 -3 Pa, the sealed alloy plate was placed in a resistance furnace, kept at 830 °C for 30 min, and then quenched by water cooling to room temperature.
[0053] The initial structure of the titanium alloy prepared in this example was characterized by scanning electron microscopy. Figure 1 The results show that the initial structure of the titanium alloy prepared in this embodiment is an equiaxed β grain structure with an average grain size of 105.5±2.3μm.
[0054] The mechanical properties of the titanium alloy prepared in this embodiment were tested according to GB / T 228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method". The engineering stress-engineering strain curve is shown in the attached figure. Figure 2 The results show that the upper yield strength of the alloy is 456±57MPa, the lower yield strength is 398±31MPa, the tensile strength is 696±16MPa, the elongation at break is 38±2%, and the yield strength ratio is 0.57.
[0055] The electron backscatter diffraction of the scanning electron microscope was used to characterize the deformation structure of the titanium alloy prepared in this embodiment. Figure 3 The results show that the dominant deformation mechanism of the alloy is {332} <113> Twinning and dislocation slip.
[0056] The electron backscatter diffraction of the scanning electron microscope was used to characterize the deformation band in the deformation structure of the titanium alloy prepared in this embodiment. Figure 4 The results show that the alloy forms {332} <113> There is a thin layer of ω phase attached to the boundary of deformation twins.
[0057] Comparative Example 3 The main constituent elements and mass percentages of the metastable β titanium alloy provided in this comparative example are: 76.83% Ti, 21.34% V, 1.75% Al, 0.005% Fe, 0.044% O, 0.003% H, 0.008% N, 0.019% C, and the remainder are unavoidable impurity elements.
[0058] The preparation process of this titanium alloy includes the following steps: S1. Using high-purity Ti with a purity of 99.995%, high-purity V with a purity of 99.95%, and high-purity Al with a purity of 99.95% as raw materials, smelting is performed in a vacuum arc melting furnace. The smelting is repeated 5 times in total. After each smelting is completed, the titanium alloy ingot is turned over for the next smelting; S2, seal the titanium alloy ingot into a glass tube, the vacuum degree of the glass tube is 3.5×10 -4 Pa, the sealed titanium alloy ingot is placed in a resistance furnace, first heated to 1050°C, kept at this temperature for 12 hours for vacuum homogenization annealing, and then cooled to room temperature; S3. Place the glass tube containing the titanium alloy ingot after vacuum homogenization annealing in a resistance furnace, first heat it to 900°C with the furnace, keep it at this temperature for 30 minutes, then quickly smash the glass tube, use a double-roll plate and strip mill to hot-roll the titanium alloy ingot once, with a total deformation of 43.5%, and water-cooled and quenched to room temperature after hot rolling. Then use a double-roll plate and strip mill to cold-roll the hot-rolled titanium alloy plate for multiple passes at room temperature, with the roller pressure of each pass being 0.3mm and the total deformation being 62.2%; S4, the cold-rolled titanium alloy sheet is sealed in a glass tube, and the vacuum degree of the glass tube is 1×10 -3 Pa, the sealed titanium alloy plate was placed in a resistance furnace, kept at 860 °C for 30 min, and then quenched by water cooling to room temperature.
[0059] The initial structure of the titanium alloy prepared in this comparative example was characterized by scanning electron microscopy. Figure 1 The results show that the initial structure of the titanium alloy prepared in this comparative example is an equiaxed β grain structure with an average grain size of 104.7±1 μm.
[0060] The mechanical properties of the titanium alloy prepared in this comparative example were tested according to GB / T 228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method". The engineering stress-engineering strain curve is shown in the attached figure. Figure 2 The results show that the yield strength of the alloy is 462±8MPa, the tensile strength is 590±1MPa, the elongation at break is 40±3%, and the yield strength ratio is 0.78.
[0061] The electron backscatter diffraction of the scanning electron microscope was used to characterize the deformation structure of the titanium alloy prepared in this comparative example. Figure 3 The results show that the dominant deformation mechanism of the alloy is {332} <113> Twinning and dislocation slip.
[0062] The electron backscatter diffraction of the scanning electron microscope was used to characterize the deformation band in the deformation structure of the titanium alloy prepared in this comparative example. Figure 4 The results show that the alloy forms {332} <113> The boundary of deformation twins contains only a small amount of α" phase, and there is no ω phase thin layer.
[0063] Compared with Example 1 and Example 2, although the same preparation process is used, the titanium alloy composition provided by this comparative example exceeds the scope of protection of this patent application, which results in the corresponding alloy forming {332} <113> A thin layer of ω phase cannot be formed on the boundary of deformation twins, so this type of twin can only provide limited work hardening ability, which leads to a significantly higher yield strength ratio of the alloy.
[0064] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0065] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A metastable β titanium alloy having a yield strength ratio lower than 0.6, characterized in that: The constituent elements and mass percentages of the titanium alloy are: 78%-82% Ti, 18%-20% V, 0.5%-1% Fe, 0.03%-0.08% O, and the remainder is unavoidable impurity elements.
2. The metastable β titanium alloy having a yield ratio lower than 0.6 according to claim 1, characterized in that: The titanium alloy is composed of 100% β phase, and in the plastic deformation stage, stress-induced ω phase laths with thin layers of non-same variant ω phase attached to the boundaries and / or a thin layer of ω phase attached to the twin boundaries are generated. <113> Deformation twins.
3. The metastable β titanium alloy having a yield ratio lower than 0.6 according to claim 1, characterized in that: The mass percentage ratio of the Ti element to the V element in the titanium alloy is in the range of 4 to 4.5, and the sum of 0.67 times the mass percentage of the V element and 2.9 times the mass percentage of the Fe element is in the range of 13.6% to 16.3%; the mass percentage ratio of the V element to the Fe element in the titanium alloy is in the range of 18 to 35; the sum of the mass percentages of the Fe element and the O element in the titanium alloy is not higher than 1.05%.
4. The metastable β titanium alloy having a yield ratio lower than 0.6 according to claim 1, characterized in that: The mass percentages of interstitial impurity elements H, N and C in the titanium alloy are respectively lower than 0.004%, 0.015% and 0.02%.
5. A method for preparing a metastable β titanium alloy having a yield ratio lower than 0.6 according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Weigh pure Ti, pure V and pure Fe raw materials according to the constituent elements and mass percentages of the titanium alloy in any one of claims 1 to 4, and obtain a titanium alloy ingot by vacuum arc melting; S2, performing vacuum homogenization annealing treatment on the titanium alloy ingot; S3, hot rolling the titanium alloy ingot after vacuum homogenization annealing to form a hot-rolled plate, water-cooling and quenching to room temperature after hot rolling, and then performing multiple cold rolling processes on the hot-rolled plate to form a cold-rolled plate; S4, performing vacuum solution heat treatment on the cold-rolled plate, and after the solution treatment, water-cooling and quenching to room temperature to complete the preparation of the titanium alloy.
6. The method for preparing a metastable β titanium alloy having a yield ratio lower than 0.6 according to claim 5, characterized in that: In S1, the raw materials are pure Ti, pure V and pure Fe with a purity higher than 99.95%; the vacuum arc melting is repeated 3 to 5 times, and after each melting is completed, the titanium alloy ingot is turned over for the next melting.
7. The method for preparing a metastable β titanium alloy having a yield ratio lower than 0.6 according to claim 5, characterized in that: In S2, the titanium alloy ingot is placed in a vacuum higher than 3×10 -4 The temperature is raised with the furnace in a vacuum environment of 1000 Pa, kept at 1050°C for more than 10 hours, and then cooled with the furnace to room temperature.
8. The method for preparing a metastable β titanium alloy having a yield ratio lower than 0.6 according to claim 5, characterized in that: In S3, the titanium alloy ingot after vacuum homogenization annealing is placed in a vacuum chamber with a vacuum degree higher than 3×10 -4 Pa vacuum environment, the temperature is raised with the furnace, and it is kept at 900℃ for more than 30min, and then it is immediately hot-rolled by a double-roll plate and strip rolling mill with a deformation of 30%~60%. After the hot rolling is completed, it is water-cooled and quenched to room temperature; at room temperature, the hot-rolled plate is cold-rolled for multiple passes by a double-roll plate and strip rolling mill, and the roller pressure of each pass does not exceed 0.3mm, and the total deformation is 30%~70%.
9. The method for preparing a metastable β titanium alloy having a yield ratio lower than 0.6 according to claim 5, characterized in that: In S4, the cold-rolled sheet is placed in a vacuum with a degree of more than 1×10 -3 Pa vacuum environment, kept at 800℃~900℃ for 30min, and then water-quenched to room temperature.
10. The method for preparing a metastable β titanium alloy having a yield ratio lower than 0.6 according to claim 5, characterized in that: After the vacuum solution heat treatment described in step S4, the microstructure of the titanium alloy material is an equiaxed β grain structure with an average grain size in the range of 80 μm to 150 μm.
Citation Information
Patent Citations
Low elastic modulus metastable Beta-titanium alloy
CN102191408A
Metastable beta titanium alloy with low elastic modulus and preparing method thereof
CN103740982A
Ultralow interstitial transformation induced plasticity metastable beta titanium alloy and preparation method thereof
CN114990382A
High-strength and high-plasticity metastable beta titanium alloy strengthened by oxygen element and preparation method of high-strength and high-plasticity metastable beta titanium alloy
CN116397131A
Post-hot-rolling temperature control method for improving product of strength and ductility of metastable beta titanium alloy plate
CN116623113A
